RELATIONSHIP OF THE CONDITION OF THE MYOCARDIUM WITH INFRINGEMENTS THE CALCIUM AND PHOSPHORUS METABOLISM INPATIENTS WITH DIABETIC NEPHROPATHY - I.I. Topchii; V.P. Denisenko; O.M. Kirienko; P.S. Semenovykh; Yu.S. Yakimenko; V.V. Mazii; O.M. Schenyavskaya (Ukrainian Journal of Nephrology and Dialysis, 2017)
Objective: To establish the possible relationship between changes in cardiac hemodynamics and im-paired phosphate-calcium metabolism and content FGF 23.Patients and Methods: 260 people with diabetic nephropathy, 64 people with hypertension and 20 healthy individu-als were surveyed. Studied the state of the myocardium and cardiac hemodynamics, blood levels of calcium, phosphorus and FGF 23.Results and conclusions: between the state of myocardium, cardiac hemodynamics and content FGF23, phos-phorus and calcium are closely interrelated, which is likely mediated through specific receptor apparatus of myocardium and through immunoinflammatory mechanisms. However, the specific mechanisms of action system FGF23 / phosphorus-calcium exchange for anatomical and functional myocardial changes require further investigation.